Pedagogia da internacionalização da educação superior: a docência na UNILA - Woicolesco, Vanessa Gabrielle (2023)
This thesis is inserted in the scientific field of higher education, in the subfields of Internationalization of Higher Education and university pedagogy, focusing on the intersection between teaching and internationalization, and the relevance of a Pedagogy of Internationalization. The emerging contexts challenge Higher Education Institutions to develop more democratic and sustainable internationalization policies and practices based on equity. Recent research indicates that the Internationalization of Higher Education reaches a comprehensive level when it is aligned in all policies and practices of Higher Education Institutions, contributing to the improvement of the quality of teaching, research, extension and university management. From this approach, professors are fundamental actors in the internationalization process and decisive elements in this new paradigm under construction. In this thesis, teaching in higher education has been constituted as a transversal axis of investigation, in order to be understood as inseparable from the teaching-research-extensioninternationalization dimensions that permeate Higher Education Institutions nowadays. Having as a research site one of the Brazilian federal universities with international mission and vocation, the research had as a general objective to understand how teaching is configured at the Federal University of Latin American Integration - UNILA, from the perspective of a Pedagogy of Internationalization of Higher Education. Regarding the methodological approach, it is characterized as a mixed method research, carried out from the case study strategy. The data construction was carried out simultaneously between qualitative and quantitative perspectives, using semistructured interviews and questionnaires, as well as documentary research. The dialogic partners chosen were the professors working in the institution, regardless of their institutional ties. The data analysis procedures were textual discourse analysis for the qualitative data and descriptive and inferential statistics for the quantitative data, after using the chi-square test of independence to verify the association between pairs of variables. The analytical procedures revealed four central categories: characteristics and training processes of the professor working at UNILA; dimensions and perspectives of Internationalization of Higher Education from the perspective of professors; the pedagogical dimension of internationalization; and professional development of professors at UNILA. The results show that in the internationalization of Higher Education, professors are the supporting pillars of an academic architecture that must combine interdisciplinary knowledge in different fields of knowledge; the different epistemologies, knowledge and cosmovision; interculturalism; language policies and international/global perspectives. The thesis presents a proposal for the construction of a formative itinerary aimed at the professional development of teaching staff at UNILA, considering the dimensions of internationalization, bilingualism/plurilingualism, interculturalism and interdisciplinarity.